Institutional Features of Large-Scale Innovation Clusters (on the Example of Skolkovo and Silicon Valley) - E. V. Akinfeeva; B. A. Erznkyan (Управление)
An approach to territorially localized innovation clusters as large-scale economic systems with an institutional component in their structure is developed in this paper. The approach is methodologically based on the G.B. Kleiner’s system paradigm according to which systems can be presented as a set of four elements – objects, environments, processes, and projects. Identifying institutions as systems allows incorporate the institutional component in the system paradigm. Taking into account the possibility for four-element representation of institutions as systems, the institutional features of such largest innovation clusters as Russian Skolkovo and American Silicon Valley are considered.